Vatican and Africa in the 21st century: strategy, institutional presence and pastoral policy - Nagibarova, Yulia A. (Journal of the Belarusian State University. International Relations, 2026)
This article analyses the Holy See’s relationship with Africa in the 21st century. It investigates the Vatican’s institutional presence and the demographic and pastoral potential of African Catholicism. Furthermore, the study evaluates the church’s peacekeeping and humanitarian efforts and the role of African clergy in the Holy See’s global papal policies. The paper highlights Pope Francis’ strategy and the potential for policy continuity under his successor, Leo XIV, including engagement with the African episcopate, institutional appointments, and priorities for global social justice. Ultimately, the analysis demonstrates the reciprocal influence between Africa and the Vatican and underscores Africa’s central role in the church’s pastoral, diplomatic, and institutional activity.
Keywords: Vatican; Africa; Pope Francis; Pope Leo XIV